Learning to be Gay: Narrative Socialization of Young Indonesian Homosexuals - Wardana, Amika (UI Scholars Hub, 2022)
The increasing religious conservatism within Indonesian society has propelled the growth of hatred and vigilantism targeting sexual minorities—which are seen as committing an unforgiven sin—especially towards LGBTs (Lesbian, Gay, Bisexual and Transgender). This study addresses the processes that these minorities experience in order to express their sexual identities and forge social relationships with fellow same-sex queers. In specific, this study focuses on the ways young gays begin to understand and develop their sexual identity amidst a largely hostile social environment. By utilizing social media, these young gays have built digital communities for socialising with fellow gay people, as well as to express their sexual orientation while remaining concealed from other parts of society. Yet, by being forced to keep a low profile, they have also been disincentivized from paying attention to promote their civic and citizenship rights. The findings of this study are based on several qualitative interviews with young gays living in the city of Yogyakarta, Indonesia.